Rice Straw as a Fuel for Thermal Processes - Singh, Iqbal; Taggar, Monica Sachdeva (Indian Farming, 2017)
Silica in rice straw is soluble in basic solutions and as a result doesnot leach-out with water or acidic solutions like most other biomassnutrients. There is a need to study the alternative methods for the extraction of Silicon from rice straw for its use in thermal conversion processes.